Pengetahuan dan Praktik Bidan tentang Standar Pelayanan Kehamilan di Era Pandemi Covid-19 - azizah, nurul; Rosyidah, Rafhani (-)
Coronavirus 2019 (COVID-19) is a highly contagious new type of respiratory disease (pneumonia) caused by coronavirus 2 (SARS-CoV-2). All countries are making various efforts to control covid-19, but there are still many infected victims, so WHO has designated this case as a Covid-19 Pandemic. Pregnant women are more susceptible to viral infections; this is due to changes in the immune system and body anatomy. Pregnancy checks in the hospital will be a significant risk for the threat of covid-19 transmission, while services during pregnancy are essential to avoid complications that can occur during pregnancy. This study aims to identify midwives' knowledge and practice regarding the standard of pregnancy services during the Covid 19 pandemic, using a questionnaire given to midwives as health care workers. The study design used a cross-sectional study with a chi-square statistical test to determine health services barriers during the pandemic. They were analyzed descriptivelySanples took with quota sampling, with a total of 30 village midwives in Candi Sidoarjo sub-district. The research instrument used a questionnaire. This study indicates that 70% of midwives have good knowledge but do not implement standard pregnancy care during the pandemic. The analysis results show that there is no relationship between knowledge and standard practice of pregnancy services during the Covid-19 pandemic. Conclusion: Most midwives have good knowledge and do not practice standard pregnancy services during the Covid-19 pandemic. Suggestion. The next research is to identify the achievements of the pregnancy service program during the Covid-19 pandemic.